Bumblebees in Greenhouses: The Secret Pollination Weapon for Thriving Crops - Satwika, Maharaj; Ch., Asritha; Madhuri, Burjikindi; Yashaswini, Gummudala; Ramesha, N. M. (Chronicle of Bioresource Management, 2024)
Protected cultivation is the foremost method, helping growers overcome climate challenges and attain the utmost yield. However, pollination continues to be a constraining factor in greenhouse cultivation. Bumblebee pollination is crucial and effective for greenhouse conditions. Bumblebees, with their efficient pollination techniques and adaptability to greenhouse conditions, play a pivotal role in enhancing crop yields and quality. However, it also has some drawbacks to achieve sustainable pollination.